Healthcare professionals' intention to leave - Laiho Maarit; Tevameri Terhi; Vähätalo Mervi; Kallio Tomi J.; Suomi Kati (Inderscience Publishers, 2025)
The objective of this study was to examine the importance of workplace choice criteria, satisfaction with those criteria and their relationship with the intention to leave among healthcare professionals. The study is based on a large survey implemented in a private healthcare organisation. According to the results, dissatisfaction with workplace choice criteria predicts the intention to leave among healthcare professionals. However, the experienced importance of workplace choice criteria does not affect healthcare professionals' intention to leave. In order to dissuade healthcare professionals from leaving, it is important to pay attention to organisation-related practices that are under management control. For physicians, dissatisfaction with organisational factors mainly explains intention to leave. For nurses, dissatisfaction with work-life interface-related issues together with the organisational factors explains their intention to leave. Based on the findings, it is important to acknowledge that work-related factors attract healthcare professionals but are not enough to make them stay. Thus, it is suggested that employee entry and employee retention be managed separately.